Relationship Between Current Characteristics of Rocket-triggered Lightning During Different Discharge Stages - Wang Jingxuan; Zhang Yang; Chen Zefang; Sun Xiubin; Fan Yanfeng; Zheng Dong; Fan Xiangpeng; Lü Weitao; Zhang Yijun (应用气象学报)
The research on rocket-triggered lightning has made great progress since 1967. Various parts of rocket-triggered lightning are studied, but differences between initial stages of different types of rocket-triggered lightning and the relevance on each part of rocket-triggered lightning is still not well understood. Based on the rocket-triggered lightning current data obtained from Guangdong Comprehensive Observation Experiment on Lightning Discharge in Field Experiment Base on Lightning Sciences, China Meteorological Administration, two types of rocket-triggered lightning are classified considering the existence of return storke(RS)and the length of the initial continuous current(ICC). Differences of rocket-triggered lightning in different categories and the correlation between various parts are analyzed. Firstly, the difference between the rocket-triggered lightning with return strokes and the rocket-triggered lightning without return strokes is obvious. The precursor current pulse(PCP)and initial precursor current pulse(IPCP)average peak current, IPCP transfer charge, ICC average current and total transfer charge and duration of lightning with RSs are greater than those of lightning without RSs. Secondly, longer ICC duration corresponds to higher average peak current, first return charge and first RS peak current, PCP and IPCP peak current, PCP and IPCP average transfer charge of triggered lightning. It is also found that the average peak value of PCP and IPCP has the strongest correlation with ICC duration. The larger the average peak value of PCP and IPCP is, the longer the ICC duration is. It's also found that during the ascent of the rocket, the transfer charge of PCP tends to increase as the altitude of the rocket increases. There are some PCP pulse clusters that cannot produce a continuous upward leader (UPL), and it fails to produce an ICC. The average transfer charge of the PCP cluster is smaller than the average transfer charge of the initial precursor current pulse cluster (IPCP). According to the analysis of data, one of the conditions for the PCP cluster that fails to generate ICC to become IPCP is that the average transfer charge is greater than 25.91 μC.